2019
DOI: 10.1038/s41438-019-0221-8
|View full text |Cite|
|
Sign up to set email alerts
|

RhMYB108, an R2R3-MYB transcription factor, is involved in ethylene- and JA-induced petal senescence in rose plants

Abstract: Rose (Rosa hybrida) plants are major ornamental species worldwide, and their commercial value greatly depends on their open flowers, as both the quality of fully open petals and long vase life are important. Petal senescence can be started and accelerated by various hormone signals, and ethylene is considered an accelerator of petal senescence in rose. To date, however, the underlying mechanism of signaling crosstalk between ethylene and other hormones such as JA in petal senescence remains largely unknown. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 56 publications
(80 reference statements)
1
32
0
Order By: Relevance
“…In Prunus mum e, PmMYB108 (90% sequence similarity with RmMYB108 ) is positively associated with organ color ( Zhang et al, 2018 ). In R. chinensis , RcMYB108 , which is homologous to RmMYB108 (94.17% sequence similarity), was upregulated during petal senescence and shedding, and silencing of RcMYB108 altered the expression of senescence-associated genes and blocked ethylene- and JA-induced petal senescence ( Zhang et al, 2019 ). Interestingly, when Arabidopsis seeds were cultured at 4°C for 6 months, we found that the speed of seed germination and plant growth was greatly reduced (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In Prunus mum e, PmMYB108 (90% sequence similarity with RmMYB108 ) is positively associated with organ color ( Zhang et al, 2018 ). In R. chinensis , RcMYB108 , which is homologous to RmMYB108 (94.17% sequence similarity), was upregulated during petal senescence and shedding, and silencing of RcMYB108 altered the expression of senescence-associated genes and blocked ethylene- and JA-induced petal senescence ( Zhang et al, 2019 ). Interestingly, when Arabidopsis seeds were cultured at 4°C for 6 months, we found that the speed of seed germination and plant growth was greatly reduced (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant constructs were co‐transformed into yeast strain EGY48 and the transformed yeast cells were incubated on SD/‐Trp‐Ura medium for 3 days at 30 °C. The transformed yeast cells were then transferred to the SD/‐Trp‐Ura + X‐gal medium and incubated for 5 days to test the interaction between the protein and the promoters of TPSs (Zhang et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, total RNA was isolated from samples with three biological repeats, and 2 µL of the first-strand cDNA was used as template with the Step One Plus TM real-time PCR system (Applied Biosystems) using KAPA™ SYBRR FAST quantitative PCR kits (Kapa Biosystems). The RhUbi2 housekeeping gene was used as standard, which was validated in previous studies [47,48]. The primers used for determining transcript abundance are listed in Supplementary Table S3.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%